Housing afforability dynamics in Australia 2001-06 - Wood, Gavin; Ong, Rachel (Centre for Research in Applied Economics, Curtin Business School, 2009)
This paper investigates the dynamics of housing affordability in Australia over the period 2001-06 using waves 1 to 6 of the Household, Income and Labour Dynamics in Australia Survey. We utilise a discrete time hazard model approach to examine whether housing affordability stress has increased over the period 2001-06, and whether spells in housing stress are transient or persistent. The results suggest that while most Australians escape unaffordable housing circumstances, there is a minority for whom unaffordable housing circumstances are a long term experience. Panel models are employed to estimate the impacts of socio-demographic characteristics on the probability of exiting from a spell of (un-) affordable housing given (un-) affordable housing in the previous year. The model findings indicate that those with children and have no employment are more prone to persistent housing affordability stress. However, residential moves during spells of housing affordability stress tend to alleviate housing cost burdens. Survival in affordable housing has become progressively more difficult over the 2001-06 timeframe, particularly for owner purchasers. This finding is unsurprising given a house price boom and rising interest rates over the period of analysis. Residential moves are again influential, but those made by households during a spell living in affordable housing are associated with the onset of housing affordability stress.JEL Classification: R20